Corrigendum: Hauntings, homeopathy, and the Hopkinsville Goblins: using pseudoscience to teach scientific thinking - Schmaltz, Rodney; Lilienfeld, Scott O. (My University, 2017)
In the original article, there was an incorrect citation. In the third paragraph under the heading, “Aliens and Goblins”, the reference to Davis and Bloecher (1978) is incorrect. The reference should be Nickell (2006).
Keywords: scientific thinking; skepticism; pseudoscience; teaching resources; introductory psychology